Douglas Boyd conducts Handel's Messiah With Carolyn Sampson, Paula Murrihy, Allan Clayton, and Matthew Rose - Orchestre de Chambre de Paris, accentus - Handel, George Frideric (Heliox Films, Orchestre de chambre de Paris, Armor TV, 2015)
Douglas Boyd leads the Orchestre de chambre de Paris and Accentus in Handel's beloved Messiah, filmed live in 2015 at the Philharmonie de Paris. Originally conceived of as an Easter Time oratorio, the Messiah's premiere on April 13, 1742 in Dublin's Musick Hall was a resounding success: the audience of a record 700 only fit because ladies had acquiesced to the management's pleas that they wear dresses "without Hoops" in order to make "Room for more company"! The baroque oratorio's loose narrative concerns "a Subject [that] excels every other Subject", as put by librettist Charles Jennens, beginning with the prophecy of Christ's birth, continuing with the exaltation of his sacrifice for humankind, and finishing by heralding his Resurrection. By the 19th century, the heavy emphasis on Christ's early life had led to the oratorio to become an integral part of Yuletide traditions in England and the United States. In keeping with the work's cultural heritage, this Messiah performance features a stellar group of anglophone soloists (soprano Carolyn Sampson, mezzo-soprano Paula Murrihy, tenor Allan Clayton, and bass Matthew Rose) who deliver Handel's beautiful melodies and Jennens's eloquent text with ease and sincerity
Keywords: concert; Internet videos